Reflections on the Teaching of the Economic Sciences - López Sánchez, Lina Marleny; Universidad Pedagógica y Tecnológica de Colombia; Salcedo Plazas, Luis Alfonso; Universidad Pedagógica y Tecnológica de Colombia; Delgado Ruiz, Siervo Tulio; Jerez Gil, Francy Liliana; Universidad Pedagógica y Tecnológica de Colombia; Murcia Pardo, Sandra Milena; Universidad Pedagógica y Tecnológica de Colombia; Manrique Joya, Gloria Mercedes; Chaparro Cardozo, Arley Zamir; Villamil Pachón, Jonathan Steven; Universidad Pedagógica y Tecnológica de Colombia; Saavedra Najar, Rodrigo; Universidad Pedagógica y Tecnológica de Colombia; López Sánchez, Mary Luz; Universidad Pedagógica y Tecnológica de Colombia; Leguizamón Romero, José Francisco; Universidad Pedagógica y Tecnológica de Colombia; Caro, Edgar Orlando; Universidad Pedagógica y Tecnológica de Colombia (UPTC Editorial, 2023)
The Faculty of Economic and Administrative Sciences of the Pedagogical and Technological University of Colombia (Universidad Pedagógica y Tecnológica de Colombia UPTC) is preparing to commemorate the fiftieth anniversary of the creation of the  riginal programs. Therefore, the texts included in this book show the various aspects that throughout these five decades have contributed to forging and consolidating the programs that make up this academic unit. The sections that are part of the book collect various facets of this fiftieth anniversary. The text makes a journey through the events that gave rise to the creation of the faculty, going to the testimonies of those who were protagonists of its gestation. Likewise, the evolution of the faculty is traced from the interviews carried out with those who served as deans, which is part of the transformations of the teachingof economic sciences in the country. On the other hand, the book addresses the teaching-learning methods and strategies tested in the three programs of the faculty. Simultaneously, what concerns the competences and evaluation of results is examined in the context of the new demands formulated by the Ministry of National Education. The book concludes with the experience of the use of technological tools, as well as educational media and materials, in university teaching. This book is an initiative of the GIDICON research group and its seedbed SIDIC and had the enthusiastic support of the participating research professors of the UPTC. This is a fortunate opportunity to reflect on what has happened since the beginning of the seventies in the Faculty of Economic and Administrative Sciences of the UPTC, on the achievements and the protagonists of the most relevant events of this memorable period.